Epidemiological characterization of dermatophytes at a tertiary care hospital in Eastern Uttar Pradesh, India - Vandana Upadhyay; Ankur Kumar; Amresh K Singh; Jayesh Pandey (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Superficial mycosis is more prevalent in tropical and subtropical countries, such as India. Regarding this, the present study was conducted to determine the epidemiology of superficial mycosis and identify the most common dermatophytic species in this region. Materials and Methods: For the purpose of the study, a total of 220 skin scraping, nail, and hair root specimens were collected. Direct microscopic examination was performed using potassium hydroxide mount. Additionally, the samples were inoculated onto Sabouraud dextrose agar (SDA) and dermatophyte test medium (DTM). The fungal colony of each isolates was stained with lactophenol cotton blue mount, and observed under microscope for species identification. Results: Out of 220 isolates, 172 samples, obtained from 108 males 64 females, were positive for skin fungal infections by either KOH mount or culture. Furthermore, 113 isolates were identified as dermatophytes, while 59 samples were found to be non-dermatophytes. Among the dermatophytes isolated from different clinical samples, Trichophyton verrucosum (42/113, 38%) was the most common species, and Tinea corporis was the most common infection (36.2%). Conclusion: As the findings indicated, dermatophytes had an isolation rate of 78%, which is higher than normal. This can be due to the fact that the majority of the patients were from a rural background (71.7%) with a low socioeconomic status and poor personal hygiene who were exposed to climatic changes.